Carcinoma of vulva occurs not only during old age: A Series of six cases - Pant, PR; Sharma, J; Manandhar, BL; Joshi, A (Journal of Institute of Medicine Nepal, 2013)
Squamous cell carcinoma of the vulva is predominantly a disease of postmenopausal women; it accounts for 5% of all female genital malignant neoplasms. Postoperative recovery in two among the five operated patient was late as their vulval wound underwent dehiscence. Other three patients had an uneventful post operative period. Histopathology report showed Squamous cell carcinoma in all the cases. Lymphnodes was negative for malignant cells in all the cases. DOI: http://dx.doi.org/10.2126/joim.v35i1.8902 Journal of Institute of Medicine, April, 2013; 35:71-73